Assessment of in-shoe pressure: Development of a clinical user guide based on a DELPHI-derived consensus. (May 2022) - Palaya, Joshua; MacKenzie, Christopher; Pearson, Sue; Murray, Linda; Katsanos, Chloe
Highlights: F-Scan has limitations as a quantitative tool in plantar pressure measurement. Standardised approach necessary when using F-Scan to assess plantar foot ulcers. Delphi Method used to survey expert users to create an F-Scan clinical guide. Consider adopting the 14 accepted guiding statements to standardise F-Scan use. Performance limitations of the F-scan system are highlighted. Abstract: Background: The F-Scan (F-Scan System by Tekscan, Boston, USA) is an in-shoe pressure measurement device used to provide dynamic pressure, force and timing information to guide appropriate offloading of plantar foot ulcers. Despite the clinical utility of an in-shoe pressure measuring device there are some limitations in the validity and reliability of the output of the F-Scan. The aim of this study was to develop a consensus-based guideline following information provided by experienced clinicians, synthesis of research evidence and manufacturer's guidelines on the most appropriate use and interpretation of the data generated by the F-Scan to manage plantar foot ulceration. Methods: Using the Delphi method a series of sixteen consensus statements were developed following a two-step questionnaire utilising clinicians feedback, a review of evidence and the manufacturer's guidelines. Findings: Seventeen clinicians responded to the first questionnaire and 11 to the second, that included 8 podiatrists and 9 pedorthists working in the public and private sectors. Of the sixteen statements there was strong consensus for ten and moderate consensus for a further four. Only two statements failed to reach consensus and the feedback from the respondents was of great value providing sound clinical rationale for their rejection. Interpretation: The objective of this study has been achieved in developing a clear and concise set of guiding statements (Table 1) to standardise use of the F-Scan. The application of the guiding statements will encourage standardisation of practice with the aim of highlighting the limitations of the system and reducing potential systematic error in measurement from output produced.